2010
DOI: 10.1016/j.jaci.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting inhaled corticosteroid responsiveness in African American patients with asthma

Abstract: Background-African American patients suffer disproportionately from uncontrolled asthma. Treatment with an inhaled corticosteroid (ICS) is considered first-line therapy for persistent asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 51 publications
2
40
1
Order By: Relevance
“…Although differences within racial groups can further discriminate between differential ethnicities, specific phenotypes, and drug responsiveness (15,16), there has been little study of asthma therapies in study populations limited to African Americans or other ethnicities (17,18). However, data from the SMART study (a large multicenter trial examining safety of salmeterol) (3) and the current findings suggest that differential response to LABAs in African Americans exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although differences within racial groups can further discriminate between differential ethnicities, specific phenotypes, and drug responsiveness (15,16), there has been little study of asthma therapies in study populations limited to African Americans or other ethnicities (17,18). However, data from the SMART study (a large multicenter trial examining safety of salmeterol) (3) and the current findings suggest that differential response to LABAs in African Americans exist.…”
Section: Discussionmentioning
confidence: 99%
“…However, adherence rates in the trials reported were high (87.5% and 91%, respectively, for African Americans and whites), and there was no difference in adherence rates between those who had treatment failures and those who did not (90% adherence in both), suggesting that differential adherence did not play a significant role. Although study populations are often racially admixed, self-identified racial and ethnic categories are crude descriptors of individual genetic ancestry; indeed, recent studies of African Americans suggest that fewer than 5% of self-reported African Americans get misclassified when race is analyzed using ancestry informative markers (15) and that genetic ancestry does not contribute to differences in response to asthma medications among African American patients with asthma (17).…”
Section: Table 3 Causes Of Treatment Failures In African Americans Amentioning
confidence: 99%
“…[4][5][6][7][8] The Salmeterol Multicenter Asthma Research Trial suggested that African American patients receiving the long-acting b 2 -adrenergic agonist (LABA) salmeterol had a significantly increased risk of combined respiratory-related death or life-threatening events. 6 Whether patients were taking inhaled corticosteroids (ICSs) concomitantly during that study is unclear, but baseline ICS use was reported by a smaller percentage of African American (38%) versus white (49%) patients.…”
mentioning
confidence: 99%
“…Gould et al 13 reasonably concluded that global genetic ancestry might not be responsible for the differences observed in the way African Americans respond to ICS therapy, but rather than dismiss the effect of genetic variation on ICS responsiveness altogether, they aptly note that this study does not rule out the potential for local genetic effects of ancestry. These findings are yet to be determined in SAPPHIRE and will likely be forthcoming.…”
mentioning
confidence: 88%
“…Importantly, Gould et al 13 have broken new ground in applying a novel tool in the complicated process of dissecting a particularly complicated phenotype, response to drug therapy, and this might ultimately shed new light on the underlying genetic mechanisms involved.…”
mentioning
confidence: 99%